2017
DOI: 10.1086/693996
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Attraction? Intraguild Facilitation and Suppression among Predators

Abstract: Competition and suppression are recognized as dominant forces that structure predator communities. Facilitation via carrion provisioning, however, is a ubiquitous interaction among predators that could offset the strength of suppression. Understanding the relative importance of these positive and negative interactions is necessary to anticipate community-wide responses to apex predator declines and recoveries worldwide. Using state-sponsored wolf (Canis lupus) control in Alaska as a quasi experiment, we conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 99 publications
4
95
0
Order By: Relevance
“…Although previous work has reported the release of small mammal populations in response to mesopredator suppression by an apex predator (Ritchie and Johnson 2009), cyclic fluctuations in hare abundance result from a variety of factors including an interaction between forage availability and predation (Krebs et al 1995). Population regulation by predation may be strongest during the peak and decline phases of the hare cycle (Krebs et al 2001b), and densities of apex and mesopredators were likely too low during our study to affect hare abundance (Pozzanghera 2015, Sivy et al 2017a). Rather, differences in hare abundance between Denali and Susitna were more likely due to sparse and poor hare quality habitat in Susitna (Gibson et al 1984).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although previous work has reported the release of small mammal populations in response to mesopredator suppression by an apex predator (Ritchie and Johnson 2009), cyclic fluctuations in hare abundance result from a variety of factors including an interaction between forage availability and predation (Krebs et al 1995). Population regulation by predation may be strongest during the peak and decline phases of the hare cycle (Krebs et al 2001b), and densities of apex and mesopredators were likely too low during our study to affect hare abundance (Pozzanghera 2015, Sivy et al 2017a). Rather, differences in hare abundance between Denali and Susitna were more likely due to sparse and poor hare quality habitat in Susitna (Gibson et al 1984).…”
Section: Discussionmentioning
confidence: 78%
“…Thus, mesopredator density appears to have been influenced more by resource availability than by topdown suppression during our study. There was also little evidence in Denali and Susitna of localized avoidance of wolves by coyotes, and instead spatial patterns suggested that coyotes and red foxes were positively associating with wolves, presumably to exploit carrion (Sivy et al 2017a). These patterns, and the generally low range of wolf densities in our two study areas, suggest that interference competition from large carnivores may not be strong enoughto influence rates of scavenging by mesopredators in some systems.…”
Section: Discussionmentioning
confidence: 98%
“…The positive association between coyotes and wolves at coarse spatiotemporal scales may also be a result of facilitation (Figure ). Positive coyote–wolf interactions have been observed elsewhere (Atwood & Gese, , ; Paquet, , ; Sivy et al, ). However, as sympatric canid species with considerable niche overlap, coyotes and wolves are also likely to experience strong competition in which wolves frequently kill coyotes (Palomares & Caro, ; Paquet, ).…”
Section: Discussionmentioning
confidence: 53%
“…Both coyotes and lynx predate small mammals such as red squirrels (Tamiasciurus hudsonicus) and snowshoe hare (Lepus americanus), and coyotes also predate white-tailed deer (Latham, Latham, Boyce, & Boutin, 2013;O'Donoghue et al, 2001). Interspecific interactions are not necessarily mutually exclusive and may happen simultaneously within the same systems, including across separate spatial or temporal scales (Karanth et al, 2017;Sivy, Pozzanghera, Grace, & Prugh, 2017).…”
mentioning
confidence: 99%
“…Carnivores affect nutrient cycling by ingesting, excreting, and translocating available nutrients within and between habitats (Cederholm et al 2011), affect the composition and structure of ecological communities (Estes and Palmisano 1974, McLaren and Peterson 1994, Estes 1996, Allen et al 2014, and affect the abundance of other carnivores and prey (Estes 1996, Vanni 2002, Ripple et al 2014). Effects of carnivores on prey occur both directly (i.e., through predation; Estes 1996, Ripple et al 2014, andcompetition;Krofel et al 2012, Allen et al 2016a, Sivy et al 2017) and indirectly (i.e., causing shifts in habitat selection to avoid predation; Brown et al 1999, Altendorf et al 2001, Ripple and Beschta 2004, Atwood et al 2007). In addition, carnivores may affect composition and abundance of non-prey species in communities (Estes and Palmisano 1974, Hunter and Price 1992, Courchamp et al 1999, Prugh et al 2009, Allen et al 2014.…”
Section: Introductionmentioning
confidence: 99%